DESKRIPSI KECERDASAN EMOSIONAL SISWA DALAM KEGIATAN LITERASI DI SEKOLAH DASAR NEGERI 050 TARAKAN - Siti Widia Wati Ningsih; Ady Saputra; Andi Wilda Indra Nanna (Universitas Borneo Tarakan, 2025)
This research aims to describe students' emotional intelligence through literacy activities in class IV of the 050 Tarakan State Elementary School. The method used was descriptive quantitative with a sample of 99 students taken using purposive sampling technique. The data collection instrument consists of an emotional intelligence questionnaire and interview guide. The results of data analysis show that students' emotional intelligence is in the high category (63.4%), medium category (36.4%), and there are no students in the low category. Thus, it can be concluded that students' emotional intelligence is in the high category. Some additional findings include the aspect of managing emotions, the majority of students (69.7%) show high emotional intelligence in managing emotions, which shows their ability to control and respond to emotions well, the self-motivating aspect of most students is in the medium category, with a few students indicating high or low emotional intelligence. This shows that there are variations in the ability to motivate oneself, the aspect of recognizing other people's emotions. Most students also show high emotional intelligence in this regard, with a few students in the low category, and the aspect of building relationships. Students with high emotional intelligence tend to be better at building relationships. social relationships and getting along, socializing and building deep relationships.